Exploring the positive aspects of caregiving among family caregivers of the older adults in India - Mishra, Nidhi; Datti, Ravi S.; Tewari, Ashutosh; Sirisety, Maneela (Frontiers in Public Health, 2023)
Background Caregiving is a committed role that focuses on providing the required support and care to a care receiver who is either ill, disabled, or dependent to the extent that they are incapable of independent functioning. The topic of caregiving has been extensively studied worldwide, mainly focused on the negative aspects of caregiving, like caregiver stress, burden, role conflicts, and burnout among caregivers. However, limited efforts have been made to understand the positive aspects of caregiving among informal caregivers who spend most of their time in this unpaid role. The present study addresses this concern by exploring the positive aspects of caregiving among family caregivers of older persons in India. Methodology This is a qualitative study, which was conducted, using the existential-phenomenological approach. In this study, a purposive sampling technique was used, and a total of a 100 family caregivers participated from four cities in India, namely Prayagraj, Pune, Visakhapatnam, and Guwahati. Twenty-five family caregivers between the age of 30–50 years participated from each of these four cities. The data was collected using six semi-structured interview questions on positive aspects of caregiving based on the lived experiences of caregivers. The interview schedule was developed based on the PERMA model and finalized after the pilot study. Each interview took 30–50 min and was recorded and transcribed. Results The data was analyzed using thematic analysis. Some commonalities and differences were observed in the responses given by family caregivers from the four cities. Four major themes that emerged for the “Nature of positive caregiving” among participants from all four cities are “Caregiver’s attitude,” “Care and compassion,” “Roles and responsibilities,” and “Beliefs and values.” Four significant themes for the “Factors contributing to positive caregiving” are “Meaningfulness in life,” “Sense of belongingness,” “Personal growth,” and “Empathetic understanding.” Conclusion Based on the study’s findings, it can be said that the themes were associated with the PERMA model. Positive caregiving is an important indicator of caregivers’ and care receivers’ well-being. The findings have implications for planning some action research, training, and counseling programs for promoting positive aspects of caregiving among informal caregivers.